Automatic Switching of Street Light by Considering Intensity of Sunlight and Fault Detection - Magar, TT; Babar, AR; Ghatshile, S; Jagtap, P; Uplaunkar, Deepak (International Journal of Computer Sciences and Engineering, 2025)
The Internet of Things (IoT) is changing human lives by interfacing general inquiries together. A Street light is a wellspring of light on the edge of a street which turns on around night time for the solace of people. A critical preferred standpoint of street lighting joins: avoidance of setbacks and addition in security. Now– a-days Street light have transformed into a basic edge including road wellbeing. A lot of energy is devoured by street lights. So it is essential to spare the power as much as we can. The cost of energy continues growing as wastage of vitality increases. It has ended up being particularly basic for sparing force. Street light checking control is a computerized system proposed to enhance the effectiveness by means of consequently controlling the exchanging of street light. This errand depicts another new answer for street light control system. It comprises of remote innovation.